Constant and intermittent hypoxia modulates immunity, oxidative status, and blood components of red seabream and increases its susceptibility to the acute toxicity of red tide dinoflagellate. Issue 105 (October 2020) - Nam, Sang-Eun; Haque, Md Niamul; Shin, Yun Kyung; Park, Hyoung Sook; Rhee, Jae-Sung
Abstract: Hypoxia is an increasing threat to aquatic ecosystems and its impact on economically and ecologically important marine fish species needs to be studied. Especially, the consequences of hypoxia when occurring along with harmful algal blooms (HABs) are currently not well documented. In this study, we investigated the effect of constant and intermittent (daily and weekly) hypoxia on respiration, immunity, hematological parameters, and oxidative status of red seabream for 2, 4, and 6 weeks. Under constant and daily intermittent hypoxia, respiration rate significantly increased in 2 weeks compared to the control. Constant and daily intermittent hypoxia caused significant decreases in the activity of alternative complement pathway, lysozyme, and the level of total immunoglobulin (Ig), as well as significant increases in the concentrations of cortisol, hemoglobin, red blood cells, and white blood cells. A significantly higher level of malondialdehyde was measured for all hypoxia-exposed groups, indicating lipid peroxidation and oxidative stress. At 4 and 6 week, the level of glutathione and enzymatic activities of glutathione reductase and glutathione peroxidase were significantly decreased after constant and daily intermittent hypoxia challenge. The enzymatic activities of superoxide dismutase and catalase were significantly increased at 2 and 4 weeks, but they were decreased after 6 weeks by constant and daily intermittent hypoxia. Constant and daily intermittent hypoxia with subsequent non-toxin producing dinoflagellate Cochlodinium polykrikoides treatment significantly reduced the respiration rate in 3 and 24 h exposure and survival rate of red seabream. Taken together, the red seabream can be vulnerable to HABs under hypoxia condition through inhibition of immunity and antioxidant defense ability. Our findings are helpful in better understanding of molecular and physiological effects of hypoxia, which can be used in aquaculture and fisheries management. Highlights: Immune-suppression significantly enacted in red seabream exposed to constant and daily intermittent hypoxia than weekly intermittent hypoxia. Significant increase in malondialdehyde by hypoxia suggests oxidative stress. Anti-oxidative activities of red seabream significantly increased at early stages, but significantly decreased in longer exposure to constant and daily intermittent hypoxia. The resistance of red seabream to red tide dinoflagellate reduced by constant and daily intermittent hypoxia.